PES - Situational Strategic Planning - Glycemia Protocol: an Experience Report (Research, Society and Development, 2022)
The Basic Health Units (UBS) are characterized by being the main gateway of the population to the Unified Health System (SUS), through the provision of a multiprofessional service, where users can have access to various services, without having to there is a need for referral to hospitals. These services offered are aimed at preventing and promoting the health of the population. The work refers to an experience report, carried out while undergraduates of the Bachelor's Degree in Nursing at Faculdade Irecê - FAI, from 08/09/2021 to 12/23/2021. It aimed to describe the practice experienced in the Internship Supervised I, where the Situational Strategic Planning (PES) was built, and after presenting the proposal to the unit's employees, we were able to effectively implement it. It is noteworthy that the PES aims to present the current scenario and the planning for the future, as well as the objectives, goals, actions, indicators and evaluation, so that they guide the development of the activities of the health units. At the end of the Supervised Internship I, it is concluded that the aforementioned was of great importance for our personal and professional growth, is that a planned management can make health services more human, provide users with comprehensive and satisfactory assistance and facilitate professionals a better organization for work.